Revisiting the administration of family justice in the family court in Malaysia - Che Soh @ Yusoff, Roslina; Mohd Arshad, Ain Husna; Mohd Zin, Najibah (Future Academy, 2018)
A ‘family court’ is generally known as a separate division of court that specifically deals with family disputes. In regulating family matters, there is no doubt that the existence of family law as a body of law is very important. However, the effectiveness of this law also depends on the institution that administers the law. In this context, it is the family court. The administration of family justice by the family court reflects the philosophy of its creation that normally takes into consideration the unique characteristics of family institution and family conflicts. Accordingly, the family court should be vested with a comprehensive jurisdiction in family matters and must be able to handle family matters effectively. The family court is not only act as a judicial institution that determine legal issues, but it also provides holistic approach and use therapeutic jurisprudence in the resolution of family disputes. In Malaysia, where dual system of family law applies, family matters of non-Muslims are heard at the civil courts, whereas for Muslims, it is the Syariah courts. For the purpose of this paper, only the civil courts are addressed. The creation of a family court at the Kuala Lumpur High Court as a specialized division of court is among the latest development in the administration of non-Muslim family law in Malaysia. This study was conducted mainly through library-based research. Field works in the form of interview and study visit were also carried out.